The role of self-financing in achieving financial independence and academic quality in government higher education institutions in the Sultanate of Oman: An analytical study of challenges and opportunities - Al-Busaidi, Noora Ahmed; Nia, Hafida (Journal of Economic, Administrative and Legal Sciences, 2025)
Higher education institutions play a pivotal role in supporting the economic and social development of the Sultanate of Oman, significantly contributing to the supply of specialized human capital for the labor market. Given the increasing financial and economic challenges, it has become essential to adopt innovative strategies to ensure the sustainability of these institutions. Self-financing is one of the key solutions that can help reduce dependence on government funding, thereby enhancing higher education institutions’ ability to achieve financial independence and improve the quality of their educational and research services. This study aims to explore the reality of self-financing in public higher education institutions in Oman, analyzing the opportunities and challenges these institutions face in its implementation. The study also seeks to offer strategic recommendations to enhance these institutions’ capabilities in diversifying their funding sources, by exploring partnerships with the private sector, strengthening financially supported research activities, and developing academic programs aligned with market needs. Through this study, the researcher aims to make an academic contribution that deepens the understanding of self-financing as a strategic tool that enhances the sustainability of higher education institutions in the Sultanate of Oman. The study also seeks to analyze the role of self-financing in achieving a balance between financial independence and academic quality, in alignment with global trends in higher education, contributing to the active role of these institutions in achieving sustainable development. To achieve this objective, the researcher employed the descriptive-analytical method by relying on previous studies and secondary data extracted from government reports and statistics related to self-financing. Additionally, a comparative analysis of successful experiences from other countries was conducted. The study confirmed that private sector funding in this area is extremely weak, accounting for no more than 10% of total funding, and that public higher education institutions still rely heavily on government funding.